Effect of Denosumab on the in vitro bioactivity and ion release dynamics of injectable PEG/glycerol/bioactive glass based bone grafts - Ozel, Cem; Ozarslan, Ali Can; Yucel, Sevil (ELSEVIER SCI LTD, 2025)
This study represents one of the first attempt in literature to develop polymeric carrier system injectable bone graft putty materials containing both Denosumab (DEN) and bioactive glass (BG), offering a dual synergistic effect for bone regeneration. Although DEN is a clinically approved drug for systemic treatment of bone loss, its use with BG in bone graft systems in about in vitro bioactivity features has not been previously investigated. In this work, DEN and melt-quenched 45S5 BGs with different particle size ranges were added into glycerol and polyethylene glycol (PEG 400, 1500 and 3000) based carrier system. PEG/glycerol/BG based injectable bone graft putty samples, and the effects of BG size, BG amount, and incorporation of DEN in different amounts on in vitro bioactivity were comprehensively evaluated. All putty samples exhibited apatite formation after 7 days of Simulated Body Fluid (SBF) incubation, confirming in vitro bioactivity feature of samples. Following SBF incubation, putties containing smaller BG size and higher BG content in putties without DEN exhibited higher apatite deposition and crystallinity (similar to 27 %), reflecting enhanced bioactivity. Moreover, incorporation of DEN led to enhanced crystallinity (similar to 30 %) following SBF incubation, thereby reflecting improved bioactivity. Furthermore, incorporation of DEN induced additional crystal calcite formation alongside apatite formation, significantly affecting bioactivity mechanisms and ion release behavior with limited Ca2+ ion concentration in initial SBF incubation. Calcite formation was increased with higher DEN amount in putty. These findings for developed DEN-containing injectable bone graft putty hold promising potential for future bone regeneration applications in preclinical and advanced clinical studies.
Keywords: Bioactive glass; Bioactivity; Denosumab; Injectable bone graft; PEG/glycerol; Putty; Synergetic effect; CALCIUM-CARBONATE; HYDROXYAPATITE; MINERALIZATION; CERAMICS; BEHAVIOR; SURFACE; REACTIVITY; SCAFFOLDS; CRYSTALLIZATION; DEGRADATION; Materials Science